Implementasi Ekonomi Sirkuler Kelapa untuk Mendorong Paraktik Keberlanjutan di Indonesia: Tinjauan Literatur - Azizan, Muhammad; Asyraf, M (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the implementation of the coconut circular economy as a strategy to promote sustainable practices in Indonesia. As one of Indonesia's main and abundant commodities, holds great potential for application within the circular economy concept that emphasizes waste reduction, reuse, and increased resource efficiency. Through a comprehensive literature review, this study identifies various practices and initiatives that have been implemented in circular coconut management, both at the industrial and local community levels. This research also highlights the challenges and opportunities faced in developing the coconut circular economy including technological aspects and stakeholder engagement. The findings show that the coconut circular economy can not only provide ecological benefits by reducing waste and opens up new sustainable economic opportunities, particularly by creating jobs and improving community welfare. To achieve successful large-scale implementation, synergy among the government, private sector, and community is essential in formulating supportive policies and fostering innovations in technology and production systems. This study aims to provide valuable insights for policymakers, academics, and industry stakeholders to effectively harness the potential of coconut in promoting economic sustainability in Indonesia.